Assessment of Sarcopenia Related Quality of Life Using SarQoL® Questionnaire in Patients With Liver Cirrhosis - Iacob, Speranta; Mina, Victor; Mandea, Matei; Iacob, Razvan; Vadan, Roxana; Boar, Voichita; Ionescu, Georgeta; Buzescu, Dan; Gheorghe, Cristian; Gheorghe, Liana (Frontiers in Nutrition, 2022)
Introduction: Sarcopenia, malnutrition, physical deconditioning and frailty contribute to a significantly altered quality of life (QoL) in patients with cirrhosis and sarcopenia. Aim: To test and validate the SarQoL® questionnaire in patients with end stage liver disease. Methods: Consecutive patients with liver cirrhosis, admitted to our Department between May and August 2021, completed by themselves the SarQoL® questionnaire. They were evaluated for sarcopenia according to EWGSOP 2019 definition. Results: A total of 71 patients with liver cirrhosis were included into the study, with a median age of 54 years. There was a statistically significant correlation between sarcopenia and Child Pugh classes (p=0.0003); sarcopenia was present in 31.2% of patients with Child-Pugh class A, in 58.3% with class B and in 93.5% with class C. SarQoL® score was statistically significantly lower in Child-Pugh class C vs class B and class A (70.2 vs 66.5 vs 52.5 points, p=0.0002). SarQoL® score was evaluated according to different complications of cirrhosis, with statistically significant lower scores in patients with sarcopenia (p<0.0001), with ascites requiring paracentesis (p=0.0006) and in patients with hepatic encephalopathy (p<0.0001). A cut-off level of 75.9 points for SarQoL® score can accurately detect sarcopenia in patients with end stage liver disease (AUROC of 0.823, SE of 92.1%, SP of 45.5%, PPV and NPV of 66% and 83.3%, correctly classified 70.4% of cirrhotic patients with sarcopenia). Conclusions: The use of SarQoL® questionnaire in cirrhotic patients can, at the same time, evaluate quality of life and identify subjects with sarcopenia and altered QoL.